The endogenous neuropeptide calcitonin gene-related peptide after spontaneous subarachnoid hemorrhage–A potential psychoactive prognostic serum biomarker of pain-associated neuropsychological symptoms - Bründl, Elisabeth; Proescholdt, Martin; Störr, Eva-Maria; Schödel, Petra; Bele, Sylvia; Zeman, Florian; Hohenberger, Christoph; Kieninger, Martin; Schmidt, Nils Ole; Schebesch, Karl-Michael (Frontiers in Neurology, 2022)
Background The pronociceptive neuromediator calcitonin gene-related peptide (CGRP) is associated with pain transmission and modulation. After spontaneous subarachnoid hemorrhage (sSAH), the vasodilatory CGRP is excessively released into cerebrospinal fluid (CSF) and serum and modulates psycho-behavioral function. In CSF, the hypersecretion of CGRP subacutely after good-grade sSAH was significantly correlated with an impaired health-related quality of life (hrQoL). Now, we prospectively analyzed the treatment-specific differences in the secretion of endogenous CGRP into serum after good-grade sSAH and its impact on hrQoL. Methods Twenty-six consecutive patients (f:m = 13:8; mean age 50.6 years) with good-grade sSAH were enrolled (drop out n = 5): n = 9 underwent endovascular aneurysm occlusion, n = 6 microsurgery, and n = 6 patients with perimesencephalic SAH received standardized intensive medical care. Plasma was drawn daily from day 1 to 10, at 3 weeks, and at the 6-month follow-up (FU). CGRP levels were determined with competitive enzyme immunoassay in duplicate serum samples. All patients underwent neuropsychological self-report assessment after the onset of sSAH (t1: day 11–35) and at the FU (t2). Results During the first 10 days, the mean CGRP levels in serum (0.470 ± 0.10 ng/ml) were significantly lower than the previously analyzed mean CGRP values in CSF (0.662 ± 0.173; p = 0.0001). The mean serum CGRP levels within the first 10 days did not differ significantly from the values at 3 weeks (p = 0.304). At 6 months, the mean serum CGRP value (0.429 ± 0.121 ng/ml) was significantly lower compared to 3 weeks (p = 0.010) and compared to the first 10 days (p = 0.026). Higher mean serum CGRP levels at 3 weeks (p = 0.001) and at 6 months (p = 0.005) correlated with a significantly poorer performance in the item pain, and, at 3 weeks, with a higher symptom burden regarding somatoform syndrome (p = 0.001) at t2. Conclusion Our study reveals the first insight into the serum levels of endogenous CGRP in good-grade sSAH patients with regard to hrQoL. In serum, upregulated CGRP levels at 3 weeks and 6 months seem to be associated with a poorer mid-term hrQoL in terms of pain. In migraineurs, CGRP receptor antagonists have proven clinical efficacy. Our findings corroborate the potential capacity of CGRP in pain processing.